Education and the Labour Market in Canada - Li, Xiaoxue (Université d'Ottawa / University of Ottawa, 2025)
The first chapter examines how COVID-19 affected post-secondary enrolment in Canada. Using Labour Force Survey data, I find that university enrolment increased during the pandemic for younger (17-24) and older (25-39) women. For men, the effect is only present in the younger age group and is more moderate. My results suggest that for older women, it is those that work full-time that key, and the COVID effect is larger for high-skilled and telework-susceptible occupations. For younger women, it is teenagers whose families are poorer and who live just outside the core of census metropolitan areas or census agglomerations with a university that drive my findings. The second chapter examines how job stability has evolved since the Great Recession using the Canadian Labour Force Survey, a rich source of tenure data. We find that jobs have become more stable, particularly for women and low-tenure jobs. Rising educational attainment (but not ageing of the workforce) appears to play a role in explaining some of the new job stability patterns. Contrary to the findings for the U.S. labour market, job-to-job transitions are not key to our findings. Instead it is changes in the employment to non-employment transition, particularly to unemployment, that matters for low-tenure jobs and it is employer driven. The third chapter explores the source of the job stability gender gap puzzle identified in the second chapter. It delves into the underlying reasons why women's job stability, as gauged by the female retention rate, did not simply converge towards the male rate but in fact caught up to it and then regularly eclipsed it since the mid- to late 2000s. To do so, we take advantage of the richness of the Labour Force Survey tenure data. Our cross-sectional and panel analysis both indicate that compositional differences, in particular education and industry composition, are at the core of the gender gap puzzle.
Keywords: COVID-19; post-secondary enrolment; human capital model; on-line learning; cost of education; post-Great Recession; job stability; retention rate; transition rate; gender gap puzzle